Consumption Pattern of Vegetables Among Rural Households in Moro Local Government Area of Kwara State, Nigeria - O. W., Kareem,; F. O., Oladipo,; P. B. , Kharde, (Indian Journal of Extension Education, 2014)
Nutritional status of people in developing countries is not in good shape particularly the vulnerable (rural populace) and  the situation needed urgent attention. Most rural households had uneven food intake pattern throughout the year based on  season and affordability due to different income level of family. The present study conducted to determine vegetable  consumption pattern and perceived benefits among rural dwellers in Moro Local Government area of Kwara State,  Nigeria. Arandom sampling technique was used to select 102 respondents and well structured questionnaire was used for  data collection. The result indicates that 44.1 per cent were male and 55.9 per cent were female. Majority (79%) of them  was married and only 32.1 per cent had no formal education. There was a significant relationship between selected  variables and personal characteristics of respondents. Asignificant difference also existed in the consumption pattern of  vegetables among the consumers. The study however showed a low consumption rate for cucumber, cabbage and lettuce  which are not just nutritious but also medicinal. The study recommended that nutrition education should be put in place  especially in the rural areas.
Keywords: Consumption pattern; vegetables; rural households